High-progesterone environment preserves T cell competency by evading glucocorticoid effects on immune regulation - Kashiwagi, Hirofumi; Seki, Toshiro; Oshima, Shino; Ohno, Yusuke; Shimizu, Tomoka; Yamada, Soga; Katano, Nagi; Goto, Yumiko; Yasuda, Atsushi; Tsuda, Banri; Ito, Ryoji; Izumi, Shun-ichiro; et al. (Frontiers in Immunology, 2022)
Progesterone (P4) and glucocorticoid (GC) play crucial roles in the immunoregulation of a mother to accept and maintain a semi-allogenic fetus. P4 concentration increases during pregnancy and becomes much higher in the placenta than in the other peripheral tissues, wherein the concentration of cortisol (COR), the most abundant GC and a strong immunosuppressor, remains uniform throughout the rest of the body. Here, we evaluated the effect of a high-P4 environment on pregnant immunity by comparing it with COR. Naïve T cell proportion increased transiently in peripheral blood of pregnant women just after delivery and decreased after one month. T cells stimulated with superantigen toxic-shock-syndrome-1 (TSST-1) in the presence of P4 stayed in the naïve state and did not increase, irrespective of the presence of COR, and reactive T cells could not survive. Treatment of T cells with P4 without T cell receptor (TCR) stimulation transiently suppressed T cell activation and proliferation, whereas the levels remain unaltered if P4 was not given before stimulation. Comparison of the engraftment and response against specific antigens using hu-PBL-NOG-hIL-4-Tg mice showed that P4-pretreated lymphocytes preserved CD62L expression and engrafted effectively in the spleen. Moreover, they produced antigen-specific antibodies, whereas COR-pretreated lymphocytes did not. These results suggest that a high-P4 environment suppresses T cell activation and induces T cell migration into lymphoid tissues, where they maintain the ability to produce anti-pathogen antibodies, whereas COR does not preserve T cell function. The mechanism may be pivotal in maintaining non-fetus-specific T cell function in pregnancy.